Soil Conservation inside Forest Areas - Sahay, B. K. (Indian Forester, 1957)
Forest areas carry the worst type of soil and an erosive type of terrain which are in more need of intensive soil conservation measures than the waste and fallow-lands outside the forest areas. Overgrazing and recurring forest fires initiate compaction of soil and erosion. Natural regeneration cannot be secured under such conditions resulting in creation of innumerable blanks. This accentuates exposure and desiccation of the surface soil. Soil exhaustion is the most serious problem of soil conservation inside the forest areas. It is due to soil exhaustion that the pace of timber production is on such a low ebb. To combat this menace the soil conservation measures proposed in the Second Five-Year Plan inside the forest areas in Bihar have been enumerated.